A revision of erycibe (convolvulaceae) in Peninsular Malaysia / Syahida Emiza binti Suhaimi - Suhaimi, Syahida Emiza (2012)
Erycibe is a big taxon consisting about 75 taxa distributed from western India and Sri Lanka across tropical and subtropical Asia to the northern tip of Queensland, Australia. The present study is focusing on the morphology and taxonomy of Erycibe in Peninsular Malaysia. The results show that Peninsular Malaysia consists of nineteen taxa. At present, seventeen taxa have scientific names with an additional two new taxa known as Erycibe. sp. A and E. sp. B. Four taxa are endemic to Peninsular Malaysia.